Dissertation Practice : A Journal for Learning - Durkin, Diane Bennett (London : Routledge, 2025)
Dissertation Practice: A Journal for Learning is an interactive resource that promotes journaling to engender key dissertation practices, through activities and exercises. It is rooted in the view that students can use journaling to promote thought, and that the privacy of journal entries ensures comfort and familiarity. This personal context, along with the book's open prompts, allows students to engage in extended and alternative thinking. The practices suggested here offer opportunities to imagine, create, explain, rethink, analyze, and argue for a study. The book includes blank space for students to enter short pieces of writing - such as reflections, examples, range of topics, and sample annotations - to generate and review thought, and includes features such as self-assessment questions, working with your chair boxes, revision practices, and examples of students' work. As a journal of thinking, it allows students to record their thoughts as they materialize into words, provides a safe place for practice and trial, and helps them locate in one place key pieces of writing foundational to their dissertation. This is an essential resource for students in PhD and EdD programs in the social sciences and education who are using qualitative, quantitative, and mixed methods.
1. Writing as a Convergence of Thinking, Talking, and Reading2. Practices for the Problem Statement3. Writing the Literature Review4. Writing the Methodology5. Writing up Findings6. Writing the Discussion7. Reader-Based Writing: Reviewing, Revising, Sharpening, and Editing
Keywords: Academic writing; Academic writing -- Study and teaching (Higher); EDUCATION / Study Skills; EDUCATION / Teaching Methods & Materials / Social Science; EDUCATION / Research